Babesia microti Infection Inhibits Melanoma Growth by Activating Macrophages in Mice - Shu, Xiang; Nie, Zheng; Luo, Wanxin; Zheng, Yaxin; Han, Zhen; Zhang, Hongyan; Xia, Yingjun; Deng, Han; Li, Fangjie; Wang, Sen; Zhao, Junlong; He, Lan (Frontiers in Microbiology, 2022)
Babesia microti is an obligate intraerythrocytic protozoan transmitted by an Ixodes tick. Infections caused by protozoa, including Plasmodium yoelii and Toxoplasma gondii, are shown to inhibit tumor development by activating immune responses. Th1 immune response and macrophages not only are essential key factors in Babesia infection control but also play an important role in regulating tumor development. In this study, we investigated the effects of B. microti infection on melanoma in tumor-bearing mice. The results showed that B. microti infection could inhibit the growth of melanoma, significantly enlarge the spleen size (p ≤ 0.0001), and increase the survival period (over 7 days) of tumor-bearing mice. Mouse spleen immune cell analysis revealed that B. microti-infected tumor-bearing mice could increase the number of macrophages and CD4+ T cells, as well as the proportion of CD4+ T cells and M1 macrophages in the tumor. Immunohistochemical assays showed that B. microti infection could inhibit tumor angiogenesis (p ≤ 0.0032). Meanwhile, both B. microti-infected erythrocytes and culture supernatant were observed to significantly (p ≤ 0.0021) induce the mRNA expression of iNOS, IL-6, and TNF-α in macrophages. Moreover, B. microti culture supernatant could also repolarize IL-4-induced M2 macrophages to the M1 type. Overall, B. microti exerted antitumor effects by stimulating the immune system of tumor-bearing mice and inducing the polarization of immunosuppressive M2 macrophages to pro-inflammatory M1 macrophages.